Development in Remote Regions: What Do We Know? - Huskey, Lee; Morehouse, Thomas A. (ARCTIC, 1992)
This article assesses a recent body of research on economic development and socio-political change in northern and other remote regions of developed Western nations. The regions include northern Canada, Alaska, northern Scandinavia, Australia's Northern Territory, and Micronesia. Research topics covered are theoretical perspectives, resource development, Native claims, and village economies. "Remote regions" are physically, economically, and politically distant from centers of wealth and power, they are culturally or ethnically diverse and sparsely settled; and they exhibit extreme limits on their autonomy, self-sufficiency, and welfare. "Development" of these regions is defined as the overcoming of internal and external obstacles to change in conditions associated with their remoteness. The authors ask whether the research has increased our understanding of the nature of these regions and of their development problems. Their answer is generally affirmative, but they also identify specific research gaps, problems, and needs. The latter include needs for more explicit theorizing, comparative and historical approaches, and research on resource ownership, Native claims outcomes, village subsistence, and population migration.Key words: Canada, Alaska, remote regions, development, resources, Native claims, village economies RÉSUMÉ. Cet article évalue un ensemble de recherches effectutées récemment sur le développement économique et les changements socio-politiques dans la partie septentrionale et dans des régions éloignées de nations occidentales développées. Ces régions comprennent le nord du Canada, Alaska, le nord de la Scandinavie, le Territoire du Nord australien ainsi que la Micronésie. Les sujets de recherche couverts sont les vues théoriques, la mise en valeur des ressources, les revendications autochtones et les économies de village. Les régions éloignées sont, aux plans physique, économique et politique, distantes des centres de richesse de pouvoir; elles présentent une certaine diversité du point de vue ...